Implementación de contabilidad comercial en la empresa “ferransy” de la ciudad de Santo Domingo provincia De Los Tsachilas periodo de enero-marzo del 2014 - Sócola Sócola, Edita Elizabeth (2016)
This thesis entitled: "IMPLEMENTATION OF COMMERCIAL ACCOUNTING FERRANSY, SANTO DOMINGO DE LOS TSACHILAS PROVINCE, PERIOD JANUARY - APRIL 2014", with the Taxpayer Registration Number ( RUC ) No. 1714104567001 is a work adapted to the needs and business activities that the company makes and therefore facilitates knowledge of the economic situation - current financial through the Financial Statements; also constitutes a prerequisite prior to opt for Engineering degree in Accounting and Auditing. The proposed objectives of the research work in question, were hit as they developed in the Accounting Process, ie from the development of a Plan and Audit Manual in line with expectations of the entity, the Initial Inventory yielded information on the total value Assets, Liabilities and Equity available, the design of a Register of the accounts receivable that helped identify the money to be raised from sales on credit to customers, the registration and control of the inputs and outputs of the goods in stock through Kardex cards allowing to set the cost price and selling them and finally the preparation and presentation of financial statements to Mr. Rodrigo Lliquin to take the right business decisions to safeguard the liquidity, solvency and borrowing capacity of the organization. Finally we conclude that the accounting system implemented in the company contributed in a big way since allowed his manager - owner know the actual financial and economic situation in the same during the period under study, which is why it is suggested to administration to consider this proposal in order to take a proper accounting of your business and therefore provide adequate control of the capital and operating costs, to thereby safeguard the economic resources held by the entity.